2021
DOI: 10.1101/2021.11.28.470116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The phenotypic landscape of essential human genes

Abstract: Understanding the basis for cellular growth, proliferation, and function requires determining the contributions of essential genes to diverse cellular processes. Here, we combined pooled CRISPR/Cas9-based functional screening of 5,072 fitness-conferring genes in human cells with microscopy-based visualization of DNA, DNA damage, actin, and microtubules. Analysis of >31 million individual cells revealed measurable phenotypes for >90% of genes. Using multi-dimensional clustering based on hundreds of quanti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
3
13
0
Order By: Relevance
“…Thus, INTS10-13-14-C7orf26 represents a functionally and biochemically distinct module of Integrator, consistent with concurrent studies ( Figure 3H ; Funk et al, 2021 ; Pan et al, 2022 ; Wainberg et al, 2021 ). Although Integrator has been subjected to extensive structural analyses, it has been difficult to resolve the INTS10-13-14 components in relation to the rest of the complex, and inclusion of C7orf26 may facilitate future structural efforts.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, INTS10-13-14-C7orf26 represents a functionally and biochemically distinct module of Integrator, consistent with concurrent studies ( Figure 3H ; Funk et al, 2021 ; Pan et al, 2022 ; Wainberg et al, 2021 ). Although Integrator has been subjected to extensive structural analyses, it has been difficult to resolve the INTS10-13-14 components in relation to the rest of the complex, and inclusion of C7orf26 may facilitate future structural efforts.…”
Section: Resultssupporting
confidence: 89%
“…In every case, the affected ribosomal subunit corresponded to the Perturb-seq clustering across two independent sgRNAs. Although this study was in progress, another group identified C1orf131 as a structural component of the pre-A1 small subunit processome by cryo-EM, complementing our functional work (Singh et al, 2021). This validation suggests that many poorly characterized genes can be assigned functional roles through Perturb-seq, although a subset of these relationships may be explained by off-target effects (Figure S4G…”
Section: Annotating Gene Function From Transcriptional Phenotypessupporting
confidence: 61%
“…A direct association between CDC5L and securin was also found, pointing towards a direct role for the NTC in meiosis promotion. Finally, in a recent high-throughput CRISPR-based optical pooled screen, the NTC and NTC-associated components (PRP19, CDC5L, PLRG, SNW1 and BUD31) co-clustered with other mRNA splicing factors as key regulators of mitosis, confirming prior work [ 146 ]. In addition to its splicing roles, the NTC also participates directly in mitosis progression.…”
Section: Regulation Of Cell Division By Mrna Splicing Factorssupporting
confidence: 78%
“…This is typically done by sorting cells based on their expression for a particular marker. More recently, microscopy has also been utilized as a readout, for example, by measuring γH2AX foci (a marker of DNA damage) coupled with in situ sequencing [ 13 ]. Arrayed screens, which have a physical separation between each perturbation, are typically used for validation and follow‐up studies.…”
Section: Crispr ‐Based Screens In Drug Discoverymentioning
confidence: 99%